A Comprehensive Review of Global Perspectives in Science and Medicine - Alabbas, Ali Hadi Mohammed; Alzamanan, Zayed Mahdi Zayed; Alabbas, Hamad Mani lati; haydar, Mohammed Ali Al; Alsagoor, Nasser Ali Nasser; Aljali, Ali Hadi Saleh; Mohammed, Abdulaziz Mohammed Al; Abbas, Ali fares Saleh al; Haydar, Nasser Ali Mana Al; Alzamanan, Hameed Mahdi Zaied (Journal of Ecohumanism, 2024)
This article will review crossing national borders and getting acquainted with global viewpoints on science and medicine and how cultural, financial, and policy trends impact healthcare systems, medical research, and practice in various countries. This work explores the differences between countries regarding health and disease, treatment, and prevention to understand how developed and developing countries differ. We consider general problematic areas in the framework of the world’s health, including infectious diseases, chronic diseases, and the emergence of global health threats. Furthermore, the participation of other continents in the development of science and coping with threats to human health are also shown. Lastly, we hope that through this exploration, an understanding that can make science and medicine inclusive can be achieved, and hence, equitable distribution of healthcare solutions worldwide will be enhanced.